Deskripsi Pengaitan Konteks dan Pengetahuan Matematika: Tinjauan Kemampuan Literasi Numerasi - Nasrullah (Faculty of Tarbiyah and Teacher Training, 2023)
The type of research applied is qualitative research with a descriptive approach, aiming to describe the connections made by students between everyday life contexts and their mathematical knowledge to support the development of numeracy literacy skills. The subjects involved in this research are two students from the eighth grade of SMP Negeri 5 Barru. Data collection techniques used include observation, tests, and interviews. The research results indicate that the linking of context with mathematical knowledge plays a crucial role in the development of students' numeracy literacy skills. The better students are at connecting problem contexts with their mathematical knowledge, the more it supports the development of students' numeracy literacy skills. Therefore, it is essential for each student to engage in learning activities aimed at improving numeracy literacy skills and their development. This research can be extended to explore the abilities of other students related to the development of mathematical and numeracy skills. Thus, future research would be intriguing if it involves reviewing the proficiency of students in terms of developing mathematical and numeracy skills.